Blockchain Technology into Gamification on Education - Qurotul Aini; Untung Rahardja; Alfiah Khoirunisa (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2020)
As we know, Indonesia has begun to enter the era of revolution 4.0 which in that era there were many changes in all fields including the presence of blockchain technology which began to be in demand. Including in the field of education, the changes that occur in the world of education today are so significant with the commencement of the abandonment of teaching methods that still use conventional methods. Keep track of tasks by book, face to face communication, which of course will cause many losses in a certain period of time, as many tasks that have long been buried become difficult to find when needed, and the possibility of manipulation of tasks is still great. The learning method is considered as a boring and insecure way, where students cannot explore learning because the collected files can still be manipulated by other parties. So from now on the application of learning methods is changed by the concept of gamification which relies on blockchain technology. The gamification learning method was created to compensate for the times when students preferred to play games rather than learning, therefore the gamification method could be applied to management education in higher education.